Synthesis, Cytotoxicity Evaluation and Molecular Docking Studies of Xanthyl-Cinnamate Derivatives as Potential Anticancer Agents - Muthia Rahayu Iresha; Jumina Jumina; Harno Dwi Pranowo; Eti Nurwening Sholikhah; Faris Hermawan (Indonesian Journal of Chemistry, 2022)
A new series of xanthyl-cinnamate hybrid compounds (4a-d) have been synthesized and screened through in vitro assay against four human cancer cell lines, i.e., HeLa, T47D, A549, and WiDr. The results revealed that xanthone hybridization with cinnamic acid increases the selectivity of the compounds with SI values of 2.75–209.03 compared to its parent oxygenated-xanthone. Compound 1,3-dihydroxyxanthen-6-yl cinnamate (4c) showed high cytotoxic activity against WiDr cell lines with an IC50 value of 39.57 µM. Molecular docking studies revealed the possible binding modes of all hybrid compounds with EGFR protein. A complex of 3,6-dihydroxyxanthen-1-yl cinnamate (4d)-EGFR, as the best binding model, exhibited higher predicted EGFR inhibitory activity than erlotinib and oxygenated-xanthone with a ΔG and Ki value of -35.02 kJ/mol and 0.74 µM, respectively. Compounds 4c and 4d were chosen as the most potent derivates from the study.